Creating the Spatial Utilization Pattern of Traditional Villages in the Yellow River by Connecting the Heritage Corridors System with the Assessment of Tourism Potential - Xin Liu; Tangxia Wu; Ziyi Xie; Weijing Yuan; Huan Yang (Land, 2025)
Traditional villages possess considerable heritage values. Tourism provides an effective way to protect and revitalize the traditional village heritages. Current research has insufficient consideration of tourism potential when constructing the spatial utilization pattern of traditional villages. This study aims to build a spatial utilization pattern of traditional villages within the Yellow River Basin by assessing the tourism potential of each traditional village via the Combined Weight Method and identifying cultural heritage corridors through the application of the Minimum Cumulative Resistance model. The results indicate the following: (1) The traditional villages situated within the Yellow River Basin demonstrate an uneven spatial distribution, with a notable concentration in the middle and lower reaches. (2) The traditional villages located in the middle and lower reaches possess greater tourism potential compared to those found in the upstream, and they are primarily situated in Shanxi and Henan provinces. (3) In light of the cultural attributes, this study proposes a spatial utilization pattern characterized by “four core areas, seven cultural zones, and a three–tiered corridor system”. These findings promote the development of traditional villages while preserving their heritage values, strengthen the communication and integration of regional cultures, and offer practical guidance towards regional coordination and enduring development.